Traditional medicine-inspired approaches to drug discovery: can ayurveda show the way forward? - Patwardhan, Bhushan; Mashelkar, Raghunath Anant (Drug Discovery Today, 2009)
Drug discovery strategies based on natural products and traditional medicines are re-emerging as attractive options. We suggest that drug discovery and development need not always be confined to new molecular entities. Rationally designed, carefully standardized, synergistic traditional herbal formulations and botanical drug products with robust scientific evidence can also be alternatives. A reverse pharmacology approach, inspired by traditional medicine and Ayurveda, can offer a smart strategy for new drug candidates to facilitate discovery process and also for the development of rational synergistic botanical formulations.

Simultaneous determination of anthraquinone, flavonoids, and phenolic antidiabetic compounds from cassia auriculata seeds by validated UHPLC based MS/MS method - Girme, Aboli; Saste, Ganesh; Chinchansure, Ashish; Joshi, Swati; Kunkulol, Rahul; Hingorani, Lal; Patwardhan, Bhushan (Mass Spectrometry Letters, 2020)
A systematic isolation and characterization study for Cassia auriculata (CA) seeds resulted in identifying antidiabetic compounds 1,3,8-trihydroxyanthraquinone and quercetin, quercetin-3-O-rutinoside, gallic acid, caffeic acid, ferulic acid, and ellagic acid. The ultra-high-performance liquid chromatography based triple quadrupole mass spectrometry methodology was developed and validated for simultaneous identification and confirmation of these compounds from CA seeds. Multiple reaction monitoring (MRM) based quantification method was developed with MRM optimizer software for MS1 and MS2 mass analysis. The method was optimized on precursor ions and product ions with the ion ratio of each compound. The calibration curves of seven bioactive analytes showed excellent linearity (r2 ≥ 0.99). The quantitation results found precise (RSD, < 10 %) with good recoveries (84.58 to 101.42%). The matrix effect and extraction recoveries were found within the range (91.66 to 102.11%) for the CA seeds. This is the first MS/MS-based methodology applied to quantifying seven antidiabetic compounds in CA seeds and its extract for quality control purposes.